(untitled) - Goldin, Ian (Washington, D.C., 2007)
Addressing the wider public, Goldin (Director of Development Policy, World Bank) and Reinert (public policy, George Mason U.) seek to dispel what they see as misconceptions about the main dimensions of economic globalization and their impact on poverty and development, arguing that globalization can be managed so that its benefits are more widely shared and its negative impacts mitigated. They present individual chapters analyzing five economic dimensions of globalization: trade, finance, aid, migration, and ideas. For each, they examine the connections to such measures of poverty as income, health, education, empowerment, and working conditions
Keywords: International economic relations,Globalization,International trade,Emigration and immigration; Economic aspects,Developing countries